2016
DOI: 10.1021/acs.jced.5b00710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Presence of MEA on the CO2 Capture Ability of Superbase Ionic Liquids

Abstract: The miscibility of monoethanolamine (MEA) in five superbase ionic liquids (ILs), namely the trihexyl-tetradecylphosphonium benzotriazolide ([P 66614 ][Bentriz]), trihexyl-tetradecylphosphonium benzimidazolide ([P 66614 ][Benzim]), trihexyl-tetradecylphosphonium 1,2,3-triazolide ([P 66614 ][123Triz]), trihexyl-tetradecylphosphonium 1,2,4-triazolide ([P 66614 ][124Triz]), and trihexyl-tetradecylphosphonium imidazolide ([P66614][Im]) was determined at 295.15 K using 1 H NMR spectroscopy. The solubility of carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…S13, along with five different superbase ionic liquids at 295 K and 1.0 bar (CO 2 absorption after 1 h). This figure indicates that all superbase ionic liquids have an extremely high CO 2 absorption capacity in comparison to the DESs as expected, because superbase ionic liquids are specially prepared by mixing of organic superbasic proton acceptors and appropriate superacid‐based anions, which cannot be deprotonated by hydroxide ions .…”
Section: Resultssupporting
confidence: 69%
“…S13, along with five different superbase ionic liquids at 295 K and 1.0 bar (CO 2 absorption after 1 h). This figure indicates that all superbase ionic liquids have an extremely high CO 2 absorption capacity in comparison to the DESs as expected, because superbase ionic liquids are specially prepared by mixing of organic superbasic proton acceptors and appropriate superacid‐based anions, which cannot be deprotonated by hydroxide ions .…”
Section: Resultssupporting
confidence: 69%
“…For example, the use of hybrid solvents, containing amine solutions and physical solvents, may improve the efficiency of the current amine absorption processes. Hybrid solvents couple the properties of solvents to take advantage of favorable aspects of solvents while minimizing the disadvantages. , In recent years, ionic liquids (ILs), which are nonvolatile and recyclable solvents, ,, have been investigated as blends with amines and other physical solvents for carbon dioxide capture. ,, Lei et al showed that addition of omim­[TF 2 N] to methanol at a temperature of 313.2 K and pressures between 2 and 6 MPa increases the CO 2 solubility in comparison to pure methanol . Bernard et al indicated that the addition of bmim­[BF 4 ] to the aqueous monoethanolamine (MEA) solution reduces the corrosion of process equipment, which is one of the main disadvantages of the amine process .…”
Section: Introductionmentioning
confidence: 99%
“…Bernard et al indicated that the addition of bmim­[BF 4 ] to the aqueous monoethanolamine (MEA) solution reduces the corrosion of process equipment, which is one of the main disadvantages of the amine process . Furthermore, addition of an IL may help reduce the energy consumption for regeneration of amine solutions, , , while also increasing the absorption rate. ,, Haghtalab and Shojaeian showed that the enthalpy of solution of CO 2 in the MDEA + bmim­[acetate] solution is about half of the enthalpy of solution of CO 2 in the aqueous MDEA. It was concluded that replacing the aqueous media of the amine solution by the IL reduces the energy required for the solvent regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…As the first study to measure the thermophysical properties of binary mixtures of ionic liquids and alkanolamines, Geng et al reported densities, viscosities, and electrical conductivities of ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]­[PF 6 ]) with monoethanolamine (MEA) and N , N -dimethylethanolamine (DMEA) over the entire composition range at temperatures ranging from 288.15 to 323.15 K at atmospheric pressure. In following further research on binary mixtures containing MEA with ionic liquid, the density and refractive index of MEA with 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim]­[BF 4 ] are measured in the temperature range of 293.15–353.15 K by Taib and Murugesan, and in another work, densities and viscosities of this mixture at T = 293.15–333.15 K are obtained by Yin et al Also, Gonzalez-Miquel et al experimentally obtained excess enthalpies for binary mixtures of MEA and two ionic liquids, namely, 1-hexyl-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide, [Hmim]­[NTf 2 ], and 1-(2-hydroxyethyl)-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide, [OHEmim]­[NTf 2 ], over the whole range of compositions at 313.15 K. Then, McCrellis et al studied the viscosity of the equimolar mixture of MEA with trihexyl­(tetradecyl)­phosphonium bis­[(trifluoromethyl)­sulfonyl]­imide [PF 66614 ]­[NTf 2 ] at 298.15 K.…”
Section: Introductionmentioning
confidence: 99%